2010
DOI: 10.1007/s11783-010-0026-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wastewater composition on the calcium carbonate precipitation in upflow anaerobic sludge blanket reactors

Abstract: Calcium carbonate often precipitates in anaerobic reactors treating wastewater with high calcium content. The aim of this paper is to study the effect of wastewater composition on calcium carbonate precipitation in upflow anaerobic sludge blanket (UASB) reactors. Two laboratory-scale UASB reactors were operated with calcium-containing influents using acetate and carbohydrate as substrate, respectively. There was an obvious accumulation of inorganic precipitate observed in the biogranules. Observations via scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This biofilm may have also influenced the carbonate precipitation rates by higher local differences and the different polymeric substances have also been shown to influence precipitation 51 . In anaerobic sludge reactors carbonate precipitation was also shown to take place in the methanogenic layer of the granules 41 . A recent study 52 showed that a Vibrio neocaledonicus biofilm on metal was able to increase corrosion resistance by 60-fold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This biofilm may have also influenced the carbonate precipitation rates by higher local differences and the different polymeric substances have also been shown to influence precipitation 51 . In anaerobic sludge reactors carbonate precipitation was also shown to take place in the methanogenic layer of the granules 41 . A recent study 52 showed that a Vibrio neocaledonicus biofilm on metal was able to increase corrosion resistance by 60-fold.…”
Section: Discussionmentioning
confidence: 99%
“…Iron carbonate layers have also been reported in corrosion studies using iron coupons that were immersed in a methanogenic Methanobacterium culture 10 . In anaerobic waste water treatments methanogens were shown to induce precipitation and their composition and activity depends on the waste water composition 41 . Iron carbonate and iron phosphate layers have also been detected in corrosion experiments with a nonhydrogenotrophic nitrate reducing bacterium 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The higher C recovery in acetic acid and ethanol production from CO 2 ( Table 1 ) can be attributed to the fact that granular sludge used as inoculum contains a certain amount of calcium carbonate precipitates. Calcium carbonate can precipitate both in the core and on the surface of granular sludge and the surface part of the calcium carbonate precipitates contributes to the aggregation of the granules ( Yang et al, 2010 ). UASB sludge can reach a calcium carbonate content of up to 90% of the ash content in anaerobic wastewater treatment systems ( Van Langerak et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yang explained that the reason was the mass transfer impaired by the calcium blocked capillaries between the inside and the outside of the granules. On the other hand, the precipitation occurred in the core of the granular sludge treating nonacidified substrate, and, therefore, little effect on SMA could be observed [17].…”
Section: Calcium Hardness Controlmentioning
confidence: 96%